Legal and educational areas of improving civil service management systems in Ukraine and Poland - Bezpalova, O. I.; Безпалова, О. І.; Sotskyi, A.; Shkolyk , A.; Shcherbyna, V.; Shevchenko, T. V.; Шевченко, Т. В. (Cuestiones Políticas . – 2021. – Vol. 39, № 71. – P. 366-377, 2021)
Досліджено структурування концептуальних підходів до створення, розвитку та вдосконалення формування та функціонування (цивільних) систем державного управління в Україні та Республіці Польща, а також визначено шляхи і методи удосконалення національних механізмів реалізації державної кадрової політики, спираючись на сучасний позитивний польський досвід. Систематизовано позитивний досвід моделювання ефективної системи управління державною (державною) службою в Польщі, який може бути використаний в Україні для вирішення її проблем. Використано матеріали та методи аналізу документальних джерел. Зазначено, що шляхи та напрямки подальшого реформування системи управління сферою державної служби в Україні передбачають подальшу інтеграцію національної моделі державної служби та механізмів управління у цій сфері до стандартів єдиного адміністративного простору в рамках Угоди про асоціацію між Україною та Європейським Союзом.

The objective of the research was to structure conceptual approaches for the establishment, development and improvement of the formation and functioning of (civil) public management systems in Ukraine and the Republic of Poland, as well as the identification of ways and methods to improve national mechanisms for the implementation of the state personnel policy, based on the modern positive Polish experience. The positive experience of modelling an effective public (civilian) service management system in Poland that can be used in Ukraine to solve its problems has been systematized. Materials and methods were used from the analysis of documentary sources. The basis was the dialectical method of knowledge of the facts of social reality, on which formal and comparative legal approaches are largely based. Conclusions indicate that ways and directions for further reform of the management system in the field of public service in Ukraine, include the further integration of the national public service model, and management mechanisms in this area to the standards of the single administrative area within the framework of the Association Agreement between Ukraine and the European Union.

Исследовано структурирование концептуальных подходов к становлению, развитию и совершенствованию формирования и функционирования (гражданских) систем государственного управления в Украине и Республике Польша, а также выявлены пути и методы совершенствования национальных механизмов для реализации государственной кадровой политики, основанной на современном положительном польском опыте. Систематизирован положительный опыт моделирования эффективной системы управления государственной (гражданской) службой в Польше, которую можно использовать в Украине для решения ее задач. ы. Отмечено, что пути и направления дальнейшего реформирования системы управления в сфере государственной службы в Украине включают дальнейшую интеграцию национальной модели государственной службы и механизмов управления в этой сфере к стандартам единого административного пространства в рамках Соглашения об ассоциации между Украиной и Европейским Союзом.
Keywords: державна служба; public service; государственная служба; цивільна служба; civil service; гражданская служба; зарубіжний досвід; foreign experience; зарубежный опыт; Україна; Ukraine; Украина; Польща; Poland; Польша; система управління державними службами; management system of public services; система управления государственными службами